Vancomycin-resistant enterococci: therapeutic challenges in the 21st century (2020)
Vancomycin-resistant enterococci are serious health threats due in part to their ability to persist in rugged environments and their propensity to acquire antibiotic resistance determinants. Enterococci have now established a home in our hospitals and possess mechanisms to defeat most currently available antimicrobials. This article reviews the history of the struggle with this pathogen, what is known about the traits associated with its rise in the modern medical environment, and the current understanding of therapeutic approaches in severe infections caused by these microorganisms. As the 21st century progresses, vancomycin-resistant enterococci continue to pose a daunting clinical challenge.